EVALUASI KEBUTUHAN RUANG PARKIR SEPEDA MOTOR DI PT TIRTA INVESTAMA WONOSOBO - Grisela Nurinda Abdi; Aisyah Nur Jannah (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2022)
Motorcycle parking facilities at PT Tirta Investama (TIV) Wonosobo are relatively new, but its application is felt less comfortable because it is too narrow. Moreover, some motorcycles are not parked in the places that have been provided but parked on the driveway and alleyway, which makes parking access even more limited. This research is aimed to evaluate motorcycle parking facilities. Data collection was carried out by direct survey at the PT TIV motorcycle parking location from 06.00 a.m. to 06.00 p.m. on Monday and Tuesday. The evaluation method compares the parking space needed (KRP) with the available Parking Space Unit (SRP). KRP was obtained from parking characteristics by Hobbs (1995) and Indonesian Technical Guidelines for The Implementation of Parking Facilities (1996). The evaluation showed that the parking space (SRP) was lacking because only 168 SRPs were available, but 223 SRPs were needed based on the analysis. In addition, the existing alleyway needs to be widened to comply with the regulations from the Directorate General of Land Transportation. This research also provides an additional design for motorcycle parking buildings that will be carried out according to the needs and available space, which is only sufficient for 206 SRP.